Are transboundary fisheries management arrangements in the Northwest Atlantic and North Pacific seaworthy in a changing ocean? - Olga Koubrak (Resilience Alliance, 2020)
Climate change is affecting physical and biological components and processes of marine ecosystems in many ways. Resulting changes in abundance and distribution of commercially valuable species are anticipated to create or exacerbate challenges for fisheries management across national boundaries by raising questions around catch allocation, membership in the management organizations, and forms of cooperation between the organizations. In this paper we assess eight transboundary fisheries arrangements in the Northwest Atlantic and North Pacific on their preparedness to respond to climate-change driven changes. For each arrangement a three-part analysis is provided. A general introduction to fisheries management responsibilities, including species and geographic scope, is first followed by a review of how climate-related science is being supported and a discussion of how climate change is being addressed directly or indirectly in management. The review shows that none of the examined treaties and founding documents mention climate change or direct parties to include climate change in their research programs and management measures. Nevertheless, climate change is on the radar screen of all eight arrangements although adopting management approaches that do not rely on single stock assessments remains politically difficult. The seaworthiness of the eight arrangements to address climate change varies considerably. Three arrangements were categorized as the most seaworthy for investing significant resources in ecosystem-based management and climate science. Three were assessed to be moderately seaworthy for recognizing precautionary and ecosystem approaches in their treaties, or for taking steps toward this objective, as well as supporting climate science. However, they are relying on single-stock management and, at times, struggle with making decisions based on scientific evidence. Two arrangements appear to be least seaworthy because they are largely ignoring climate change and the need for an ecosystem approach in their management or have inadequate legal tools to address these needs effectively.